Recovering groundwater for wetlands from an anthropogenic aquifer - Hatch, Christine E.; Ito, Erika T. (Frontiers in Earth Science, 2022)
Freshwater wetlands are groundwater-dependent ecosystems that require groundwater for saturation, for wetland plants and creatures, for maintenance of wetland soils, and thermal buffering. With worldwide wetland area in decline for decades if not centuries, finding and restoring wetlands provides enormous ecosystem and public benefits, yet so often these projects fail to yield self-sustaining wetland ecosystems. One reason is that restored wetlands are often built in places that are neither wet enough nor possess the underlying geology to sustain them, and they dry out or require continual (expensive!) water inputs. Massachusetts is making the best of a challenging situation for the declining cranberry farming industry: while competition from less expensive land and more productive varietals shifts cranberry production to other locations, everything under historic cranberry farms is ripe for resilient wetland restoration projects. These low-lying water-rich areas are underlain by glacial geology (peats and clays) that are ideal for holding water, they possess historic seed banks of wetland plants and large accumulations of organic and hydric soils, and are currently sought-after by a statewide restoration program, for which these results provides critical information for restoration design, enabling practitioners to maximize the capture and residence time of groundwater inputs to sustain the future wetland. In this paper, we investigate the human legacy of cranberry farming on the surface of a wetland as it has created a unique hydrogeologic unit: the anthropogenic aquifer. Water moves through an anthropogenically constructed aquifer in specific and predictable ways that were engineered to favor a monoculture of cranberry plants on the surface of what once was a peatland. In order to restore this landscape to a functioning freshwater wetland, every property of the anthropogenic aquifer must be reversed. We detail observational, thermal, hydrologic, geologic and isotopic evidence for the location of groundwater inflows to Foothills Preserve in southeastern Massachusetts. The specific properties of the Anthropogenic aquifer, and the location and magnitude of groundwater discharge at this location provide crucial information for practitioners when designing plans for a self-sustaining, resilient restored freshwater wetland on this site.